Recent Innovations of Mesoporous Silica Nanoparticles Combined with Photodynamic Therapy for Improving Cancer Treatment - Doaa Sayed Nady; Afnan Hassan; Muhammad Umair Amin; Udo Bakowsky; Sherif Ashraf Fahmy (MDPI AG, 2023)
Cancer is a global health burden and is one of the leading causes of death. Photodynamic therapy (PDT) is considered an alternative approach to conventional cancer treatment. PDT utilizes a light-sensitive compound, photosensitizers (PSs), light irradiation, and molecular oxygen (O2). This generates cytotoxic reactive oxygen species (ROS), which can trigger necrosis and/ or apoptosis, leading to cancer cell death in the intended tissues. Classical photosensitizers impose limitations that hinder their clinical applications, such as long-term skin photosensitivity, hydrophobic nature, nonspecific targeting, and toxic cumulative effects. Thus, nanotechnology emerged as an unorthodox solution for improving the hydrophilicity and targeting efficiency of PSs. Among nanocarriers, mesoporous silica nanoparticles (MSNs) have gained increasing attention due to their high surface area, defined pore size and structure, ease of surface modification, stable aqueous dispersions, good biocompatibility, and optical transparency, which are vital for PDT. The advancement of integrated MSNs/PDT has led to an inspiring multimodal nanosystem for effectively treating malignancies. This review gives an overview of the main components and mechanisms of the PDT process, the effect of PDT on tumor cells, and the most recent studies that reported the benefits of incorporating PSs into silica nanoparticles and integration with PDT against different cancer cells.